The Influence of Lifestyle and Conformity on the Performance of Phicos Group IT Company Employees - Akbar Prasetyo; Yuhastina Yuhastina; Abdul Rahman (Budapest International Research and Critics University, 2022)
The high salary of employees will not automatically be directly proportional to their performance. A high salary actually triggers a high lifestyle as well. this study aims to determine whether there is an influence of lifestyle on the performance of IT employees of the Phicos Group company; knowing whether or not there is an influence of peer group conformity on the performance of the IT company employees of Phicos Group; as well as knowing whether there is an influence between lifestyle and peer group conformity on the performance of IT employees of the Phicos Group company. This study was designed using a quantitative research design using a descriptive correlational method. The data that has been obtained is then processed with the help of SPSS 25.0 software for windows. Since the number of employees in Phicos Group is 50 people, the researchers used a non-probability sampling technique with a saturated sampling technique, which means that all populations were used as samples in the study. The data collection techniques used questionnaires and interviews. The results showed that the lifestyle variable had a significant negative effect on employee performance. The smaller the value of lifestyle and conformity possessed by employees, it will increase employee performance and vice versa. The results obtained for the conformity variable have no significant effect on increasing or decreasing employee performance. Meanwhile, lifestyle and conformity together have a significant negative effect on employee performance. This means that the higher the lifestyle and conformity, the lower the employee's performance.